POLA SOSIALISASI PERGURUAN TINGGI DALAM MENINGKATKAN JUMLAH PENERIMAAN MAHASISWA BARU PADA IAIN PALU - Sofyan Bachmid; Hamka (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2018)
This article discusses the effectiveness of the new student admission socialization program on the decision of the prospective student to enroll in the State Islamic Institute (IAIN) Palu. The problem studied is How are the efforts of socialization of new student admissions applied at IAIN Palu? What is the most effective socialization attempt for student candidate's admission at IAIN Palu? This research uses survey research design combined with descriptive qualitative analysis model. Data collection using questionnaire method supported by interview and collecting a documentations. The results showed that the socialization efforts applied in IAIN Palu was by utilizing mass media and school visit. An effective efforts of socialization for introducing institutions to the public is unprogrammed in schedules, they used word to word (door to door) and publicity promotion. Nevertheless, regular programmed socialization models are held regularly every day before the admission of new students, usually used advertising and “personal selling” through visits to schools, is still quite effective. While the main consideration factor for enrolling in IAIN Palu is the availability of courses appropriate to their interests.